تقنين العملة الافتراضية في ظل التنمية المستدامة و التحول الاقتصادي - دولة الإمارات العربية المتحدة أنموذجاً: REGULATING VIRTUAL CURRENCY IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT AND ECONOMIC TRANSFORMATION - THE UNITED ARAB EMIRATES AS A MODEL - Al-Hajj Al-Dush, Al-Hajj Muhammad (I-iECONS e-proceedings, 2023)
يأتي هذا البحث في ظل التنمية المستدامة وضرورة ان التحول الاقتصادي في دولة الامارات العربية المتحدة من خلال الوقوف على تقنين التعامل بالعملة الافتراضية بوصفها نازلة فقهية تتماس مع الموروث الفقهي الإسلامي استندت عملية التقنين الى اجتهاد اوجدته الضرورة الفقهية للعملة الافتراضية في المجتمع الاماراتي و بقية العالم كما استند المشرع الاماراتي استراتيجيات الدولة الاقتصادية الاتحادية والولائية مثل : مئوية الامارات 2071 واستراتيجية أبو ظبي للتحول الرقمي 2025م واستراتيجية الإمارات للتعاملات الرقمية (بلوك تشين) 2021 م ... وغيرها من الاستراتيجات تسعى لتحقيق ضرورات التحول الاقتصادي والتنمية المستدامة في النطاق المحلي والعالمي بوصف العملة الرقمية مخرج من مخرجات تطور الاقتصاد العالمي. في البحث، تم اتباع المنهج التحليلي لنصوص المشرع الإماراتي المتصلة بالتعامل بالعمُلات الافتراضية بدولة الامارات العربية المتحدة كالقانون رقم (4) لسنة 2022م بشأن تنظيم الأصول الافتراضية في إمارة دبي بوصفه أول تقنين في التعامل بالأصول الافتراضية في دولة الإمارات العربية والمنطقة العربية والإسلامية والقرار الوزاري رقم 111 لسنة 2022، وقد استخدمت المنهج الاستقرائي عند الحديث عن التكييف الفقهي والقانوني للنقود الافتراضية، خلص البحث الى نتائج أهمها: ان المشرع الإماراتي له السبق في المنطقة العربية والإسلامية في تقنين العملة الافتراضية حينما أخذ بمستند فقهي في تكييف العملة الرقمية واضح بوصفها أصولاً مالية افتراضية. كما سلك المُشرع الإماراتي سَلك مَسلكاً قانونيا وسطاً بين الاعتراف بالعملات الإفتراضية كضرورة من ضرورات التحول الإقتصادي الرقمي والتنمية المستدامة والتخفيف من إشكالية تحمُل المسؤولية عند حدوث مضاربات أو أخطاء تُلابس التعامل من الجهات المُصرح لها بالعمل في مجال العملات الرقمية الافتراضية بالدولة . واصي البحث بضرورة اصدار تشريعات اتحادية في دولة الامارات العربية المتحدة، وقوانين واضحة في الدول العربية والإسلامية في مجال العملة الافتراضية. This research comes in the context of sustainable development and the necessity of economic transformation in the United Arab Emirates (UAE) by addressing the regulation of virtual currency as a religious issue that aligns with Islamic jurisprudential heritage. The regulation process is based on Islamic jurisprudence, necessitated by the use of virtual currency in Emirati society and the rest of the world. The Emirati legislature also relies on federal and emirate-level economic strategies such as the UAE Centennial 2071, Abu Dhabi's Digital Transformation Strategy 2025, and the UAE's Digital Transactions (Blockchain) Strategy 2021, among other strategies, aiming to achieve the requirements of economic transformation and sustainable development at both local and global levels using digital currency as a way to advance in the global economic landscape. In this research, an analytical approach was followed concerning the Emirati legislations related to virtual currency usage in the UAE, such as Law No. (4) of 2022 regarding the regulation of virtual assets in the Emirate of Dubai, which marked the first regulation of virtual assets in the UAE and the Arab and Islamic region. Ministerial Decision No. 111 of 2022 was also used. An inductive approach was used when discussing the legal and jurisprudential adaptation of virtual money. The research yielded several key results, including the fact that the Emirati legislature has taken the lead in the Arab and Islamic region by regulating virtual currency, basing this regulation on clear jurisprudential principles regarding virtual financial assets. The Emirati legislature has taken a middle ground legally by recognizing virtual currencies as a necessity for digital economic transformation and sustainable development while mitigating the responsibility issues that may arise in cases of disputes or errors in virtual currency dealings by authorized entities in the country. The research emphasizes the need for federal legislation in the UAE and clear laws in Arab and Islamic countries regarding virtual currency.